HYDROXYL IN MANTLE OLIVINE XENOCRYSTS FROM THE UDACHNAYA KIMBERLITE PIPE - Koch-Müller M.; Matsyuk S.S.; Rhede D.; Wirth R.; Khisina N. (My University, 2006)
The incorporation of hydrogen in mantle olivine xenocrysts from the Udachnaya kimberlite pipe was investigated by Fourier-transform infrared spectroscopy and secondary ion mass spectrometry (SIMS). IR spectra were collected in the OH stretching region on oriented single crystals using a conventional IR source at ambient conditions and in situ at temperatures down to −180°C as well as with IR synchrotron radiation. The IR spectra of the samples are complex containing more than 20 strongly polarized OH bands in the range 3,730–3,330 cm−1. Bands at high energies (3,730–3,670 cm−1) were assigned to inclusions of serpentine, talc and the 10 Å phase. All other bands are believed to be intrinsic to olivine. The corresponding point defects are (a) associated with vacant Si sites (3,607 cm−1 E || a, 3,597 E || a, 3,571 cm−1 E || c, 3,567 E || c, and 3,556 E || b), and (b) with vacant M1 sites (most of the bands polarized parallel to a). From the pleochroic behavior and position of the OH bands associated with the vacant M1 sites, we propose two types of hydrogen—one bonded to O1 and another to O2, so that both OH vectors are strongly aligned parallel to a. The O2–H groups may be responsible for the OH bands at higher wavenumbers than those for the O1–H groups. The multiplicity of the corresponding OH bands in the spectra can be explained by different chemical environments and by slightly different distortions of the M1 sites in these high-pressure olivines. Four samples were investigated by SIMS. The calculated integral molar absorption coefficient using the IR and SIMS results of 37,500±5,000 L mol H2O cm−2 is within the uncertainties slightly higher than the value determined by Bell et al. (J Geophys Res 108(B2):2105–2113, 2003) (28,450±1,830 L mol H2O cm−2). The reason for the difference is the different distributions of the absorption intensity of the spectra of both studies (mean wavenumber 3,548 vs. 3,570 cm−1). Olivine samples with a mean wavenumber of about 3,548 cm−1 should be quantified with the absorption coefficient as determined in this study; those containing more bands at higher wavenumber (mean wavenumber 3,570 cm−1) should be quantified using the value determined by Bell et al. (J Geophys Res 108(B2):2105–2113, 2003).
Keywords: OH− IN OLIVINE; IR SPECTROSCOPY; SYNCHROTRON IR; SIMS; POINT DEFECTS